Analisis Perataan Laba pada Perusahaan Non Manufaktur - Lila Sapta Adi Kusuma; Paskah Ika Nugroho (Jurnal Manajemen Maranatha, 2013)
The aim of this research is to analyze income smoothing practices in non manufacturing companies listed in Indonesian Stock Exchange (BEI/IDX) using time period 2007 until 2011. Data were collected from www.idx.co.id and Indonesian Capital Market Directory (ICMD) and 73 samples were used. Eckel index was usedto compute income smoothing. The result of this research show that 22 companies conduct income smoothing practices and 51 companies didn’t. Construction companies have highest percentage (66.66%) in income smoothing practices.